Proposed Fault Tolerant New Irregular Augmented Shuffle Network - Gupta, Amardeep; Bansal, P K (Malaysian Journal of Computer Science, 2011)
Multistage Interconnection Networks (MINs) are playing a vital role in real time applications. The MIN with N processors and N memory modules has the complexity as O (N log2 N). In real time applications it is important to consider time dependent reliability i.e. R (t) and mean time to failure i.e. MTTF. The imperfect coverage is defined as the probability that the system successfully reconfigures under component faults. This concept is important in considering the reliability of MINs because as the size of MIN increases the number of components increases and the probability for an occurrence of uncovered fault increase. In this paper a new class of Irregular Fault Tolerant MIN named as New Irregular Augmented Shuffle Network (NIASN) has been introduced and studied. This MIN provides better Bandwidth, Probability of acceptance, Processing Power, Processor Utilizations, Through Put and Permutation passable without Faults and with Faults in the Network and reliability as compared to popular MINs like IASN, ASEN-2 and ABN.